TOLOK UKUR DEMOKRASI PANCASILA DALAM MEMBENTUK UNDANG-UNDANG PEMILU LEGISLATIF - Sri Handayani SH.,M.Hum (Kajian Hukum, 2016)
The purpose of this research is to find a benchmark in producing legislation legislative elections based on Pancasila Democracy, as well as to determine the legislative election laws in every election is always different characters, prouk laws are made in order to meet immediate needs only.This research was conducted by the research is a research library and we also do field research. In the research literature to use the means of study documents for secondary data, while the field research was conducted to obtain primary data with qualitative approach with interviews.The results showed that: the formation of Law political field is not using the model as described in figures and tables, so it is not in accordance with the concept of rule of law as mandated in the constitution (Constitution NRI 1945) and not in accordance with the ideology of Pancasila as the foundation of philosophical. Keywords: Pancasila democracy, legislative elections, benchmarks